Analisis Indikator Kimia dan Fisika Air Untuk Menentukan Kualitas Air di Sub Daerah Aliran Sungai Biyonga Provinsi Gorontalo - Dunggio, Iswan; Musa, Weni JA; Iyabu, Hendri (Jambura Journal of Chemistry, 2024)
This study aims to determine the environmental quality in Biyonga Sub Watershed based on chemical and physical water quality characteristics. The research was conducted for 3 months in 3 parts of Biyonga sub-watershed area in Gorontalo Regency. Water quality was measured directly in the field and in the laboratory. Sampling was carried out in the upstream, middle and downstream areas of the Biyonga sub-watershed. Parameters tested were temperature, pH, TSS, BOD, COD, DO, nitrate, total nitrogen and total coliform. The results of the analysis in the upstream part of the Biyonga sub-watershed in the village of Tapalulo (point 1) showed that the COD and BOD parameters did not meet the standard requirements. Furthermore, in the middle part of Biyonga village (point 2) and in the downstream part of Biyonga sub-watershed, the TSS, COD, BOD and DO parameters are above the quality standards or do not meet the water quality standards. The accumulation of agricultural activities, domestic activities and small industries producing liquid wastes are the main causes of the lower water quality in the downstream part of the Biyonga sub-watershed. Based on the results of chemical and physical water tests, the water sources in the middle and lower reaches of the Biyonga River cannot be used as freswater sources